A Pyridazine-Based Fluorescent Probe Targeting Aβ Plaques in Alzheimer’s Disease - Yong Dae Park; Jeum-Jong Kim; Sungbeom Lee; Chul-Hong Park; Hyoung-Woo Bai; Seung Sik Lee (Journal of Analytical Methods in Chemistry)
Accumulation of β-amyloid (Aβ) plaques comprising Aβ40 and Aβ42 in the brain is the most significant factor in the pathogenesis of Alzheimer’s disease (AD). Thus, the detection of Aβ plaques has increasingly attracted interest in the context of AD diagnosis. In the present study, a fluorescent pyridazine-based dye that can detect and image Aβ plaques was designed and synthesized, and its optical properties in the presence of Aβ aggregates were evaluated. An approximately 34-fold increase in emission intensity was exhibited by the fluorescent probe after binding with Aβ aggregates, for which it showed high affinity (KD = 0.35 µM). Moreover, the reasonable hydrophobic properties of the probe (log P = 2.94) allow it to penetrate the blood brain barrier (BBB). In addition, the pyridazine-based probe was used in the histological costaining of transgenic mouse (APP/PS1) brain sections to validate the selective binding of the probe to Aβ plaques. The results suggest that the pyridazine-based compound has the potential to serve as a fluorescent probe for the diagnosis of AD.